Powtoon Media in the Whatsapp Group Application on Dental Hygiene Behavior in Primary School Children - Primawati, Rena Setiana; Robbihi, Hilmiy Ila (Center of Excellent (Pusat Unggulan Iptek), 2024)
Preventive measures such as brushing teeth are still considered not good for children. According to the Indonesian Ministry of Health's Data and Data Center in 2018, it was stated that tooth brushing behavior based on age groups in Indonesia, namely the daily brushing behavior of children aged 10-14 years, had a percentage of 96.5% with the percentage of correct tooth brushing time being 2.1%. Riskesdas states that the percentage of brushing teeth correctly is 2.8%. Promotional efforts that can be made are Dental Health Education. Apart from being carried out on children, this effort can also be carried out on parents, especially mothers. Powtoon as a multimedia application that can be used as a learning medium has several advantages, including very interesting animation features such as handwritten animation, cartoon animation and lively transition effects as well as easy timeline management. The research method and stages are development research to produce media products, then to see the effect of media use, a quasi-experimental method with one group pretest and posttest design is used. Research Results: Powtoon media for dental health education because of FGD with media experts, health promotion experts and dental health promotion media has been created with the results of expert validation and declared suitable for use as a media for Dental Health Education. Test the influence of powtoon media on children's teeth brushing practices and parents' knowledge using Wilcoxon test analysis with a p-value of 0.000 < 0.005, which means there is a significant influence.